Hyperexcitable superior colliculus and fatal brainstem spreading depolarization in a model of Sudden Unexpected Death in Epilepsy. Issue 2 (19th January 2022) - Cain, Stuart M.; Bernier, Louis-Philippe; Zhang, Yiming; Yung, Andrew C.; Kass, Jennifer; Bohnet, Barry; Yang, Yi; Gopaul, Rayshad; Kozlowski, Piotr; MacVicar, Brian A.; Snutch, Terrance P.
Abstract: Cardiorespiratory arrest and death in mouse models of sudden unexpected death in epilepsy occur when spreading depolarization is triggered by cortical seizures and then propagates to the brainstem. However, the critical brain regions and the specific changes required to allow spreading depolarization to propagate to the brainstem under the relatively rare circumstances leading to a fatal seizure are unknown. We previously found that following cortical seizure-inducing electrical stimulation, spreading depolarization could occur in both the superior and inferior colliculi in Cacna1a S218L mice, but was never observed in wild-type animals or following non-seizure-inducing stimuli in Cacna1a S218L mice. Here, we show that optogenetic stimulation of the superior/inferior colliculi in Cacna1a S218L mice induces severe seizures, and resulting spreading depolarization in the superior/inferior colliculi that propagates to the brainstem and correlates with the respiratory arrest followed by cardiac arrest. Further, we show that neurons of the superior colliculus in Cacna1a S218L mice exhibit hyperexcitable properties that we propose underlie a distinct susceptibility to spreading depolarization. Our data suggest that the susceptibility of the superior colliculus to elicit fatal spreading depolarization is a result of either genetic or seizure-related alterations within the superior colliculus that may involve changes to structure, connectivity and/or excitability. Abstract : See Gonzalez-Sulser (https://doi.org/10.1093/braincomms/fcac097 ) for a scientific commentary on this article. Cacna1a S218L mice are susceptible to spontaneous, fatal seizures and premature death. Co-stimulation of the superior and inferior colliculi in Cacna1a S218L mice initiates a spreading depolarization cascade that propagates to the brainstem correlating with respiratory arrest. Superior colliculus neurons display hyperexcitable action potential firing not observed in inferior colliculus neurons. Graphical Abstract: